The miraculous journey of Edward Tulane - DiCamillo, Kate; Ibatoulline, Bagram (London Walker Books, 2008)
Edward Tulane, a cold-hearted and proud toy rabbit, loves only himself until he is separated from the little girl who adores him and travels across the country, acquiring new owners and listening to their hopes, dreams, and histories
Age Range: 7 to up
A Junior Library Guild selection
Keywords: Toys -- Fiction; Rabbits -- Fiction; Love stories; Listening -- Fiction; Adventure stories; Toys -- Juvenile fiction; Rabbits -- Juvenile fiction; Love stories; Listening -- Juvenile fiction; Adventure stories